Mitochondrial membrane potential played crucial roles in the accumulation of berberine in HepG2 cells. Issue 4 (26th April 2019) - Li, Qiao; Zhou, Ting; Liu, Chang; Wang, Xiao-Yu; Zhang, Ji-Quan; Wu, Fei; Lin, Ge; Ma, Yue-Ming; Ma, Bing-Liang
Abstract : Berberine is a natural alkaloid that has antineoplastic effects. However, in hepatoma cells like HepG2, the expressions of uptake transporters are minimal but efflux transporters are relatively high. Hence, how berberine enters and reaches a cytocidal concentration remains to be elucidated. In the present study, we revealed the accumulation mechanism of berberine in HepG2 cells. Cell organelles were isolated based on differential centrifugation; berberine concentration was measured using a liquid chromatography-tandem mass chromatography method or flow cytometry. Subcellular distribution of berberine was observed using a laser scanning confocal microscopy. The results showed that berberine was concentration-, temperature-, and time-dependently taken up and accumulated in HepG2 cells. Membrane drug transporters and cell membrane potential had limited effects in berberine uptake. However, qualitative and quantitative studies showed that berberine was enriched in the mitochondria; inhibition of mitochondrial membrane potential (MMP) by carbonyl cyanide 3-chlorophenylhydrazone (CCCP) significantly decreased the intracellular berberine by up to 70%. More importantly, MMP not only significantly enhanced berberine uptake driven by cell membrane potential ( P <0.01) but also inhibited p-glycoprotein (P-gp)-mediated berberine efflux ( P <0.01). In brief, our results for the first time showed that MMP played crucial roles in berberine accumulation in HepG2 cells.